Tilia species (linden) exert anti-cancer effects on MIA PaCa-2 cells through the modulation of oxidative stress and inflammation - Gamze Yüksel; Yağmur Özhan; Dilara Güreşçi; Etil Güzelmeriç; Nisa Beril Şen; İpek Bedir; Onur Senol; Gizem Emre; Dilek Telci; Vilma Petrikaitė; Hande Sipahi (Scientific Reports)
Abstract This study investigated the anti-cancer effects of the chemically characterized Tilia species (linden) on MIA PaCa-2 cells by analyzing various cancer-triggering mechanisms, including oxidative stress and inflammation status. Extracts from the flowers, bracts, and inflorescences of T. cordata, T. platyphyllos, T. rubra, and T. tomentosa were evaluated for antioxidant activity; subsequently, their ability to mitigate inflammation was assessed through in vitro nitrite assays in LPS-induced RAW264.7 cells. The anticancer potentials of the extracts against MIA PaCa-2 pancreatic cancer cells were investigated in 2D (cytotoxic effect) and 3D (effect on spheroid growth) models in vitro. All investigated Tilia species displayed remarkable antioxidant activity and significantly inhibited LPS-induced nitrite, IL-6, and PGE2 production. Extract from T. rubra bracts showed the highest cytotoxic activity against MIA PaCa-2 cells with an IC50 value of 0.16 mg/mL, as well as the most significant delay on spheroid growth, which was further confirmed through the arrest in cell cycle. In the Annexin V cell death assays of T. rubra, cells treated with the flower extract exhibited the highest rate of necrotic population with 66.53%. Overall, our results highlight a potential use for Tilia extracts, particularly T. rubra, in pancreatic cancer treatment by modulating cell death.